La ética en la publicidad de las empresas multinacionales - Rivadeneira-Moreira, Julio César (Editorial Grupo AEA, 2022)
This article contains issues related to ethics in the advertising activities of multinational companies, particularly those related to misleading and irresponsible advertising, possible calls for attention affecting specific social groups and the competitive market. The objective of the research is to analyze how ethics intervenes in advertising proposed at a global level by multinational companies and the consequences of its scope. The research methodology is of a bibliographic type, by establishing a compilation of data obtained from various sources with an analytical approach to describe characteristics found in the advertising of multinational companies. In the results it is possible to appreciate a comparison of marketing strategies applied by different companies recognized worldwide that alter the reality of their products and services. Regarding the discussion, it is found that currently there are several multinational companies which provide misleading advertising in order to attract the consumer's attention, creating greater skepticism in society and generating doubts about acquiring certain products. Finally, it is understood the essential impact of ethics when presenting advertisements in order not to break the trust between stakeholders and the market, by taking more responsibility in the filter of acceptance in their advertisements.